PREPARATION AND TESTING RESULTS OF A LIQUID HYDROCARBON SOLUBLE CORROSION INHIBITOR - Khalilov Jamshid Akmal ugli (European Science Publishing, 2024)
In this work, the production of corrosion inhibitors through the reaction of fatty acids and the production of amines on the basis of organochlorine compounds released from JSC "Navoiyazot" was conducted. The results obtained based on the samples were IR spectrum, NMR spectrum, scanning electron studied and analyzed using microscopic and elemental analysis.
Keywords: Corrosion inhibitors, nitrogen, organic compounds, fatty acids, gas- condensate well, temperature, mass, level of protection.